Higher‐order structure of the 30‐nm chromatin fiber revealed by cryo‐EM. Issue 11 (5th October 2016) - Zhu, Ping; Li, Guohong
Abstract: Genomic DNA is hierarchically packaged into chromatin in eukaryotes. As a central‐level chromatin structure between nucleosomal arrays and higher order organizations, 30 nm chromatin fiber, and its dynamics play a crucial role in regulating DNA accessibility for gene transcription. However, despite extensive efforts over three decades, the higher‐order structure of the 30 nm chromatin fiber remains unresolved and controversial. We have recently reconstituted the 30 nm chromatin fibers from 12 nucleosomal arrays in vitro in the presence of linker histone H1, and determined their cryo‐EM structures at resolution of 11 Å (Song et al., Science 344, 376–380). Here, we briefly reviewed the higher‐order structure studies of chromatin fibers, mainly focusing on the insights from the cryo‐EM structures we recently solved. © 2016 IUBMB Life, 68(11):873–878, 2016